Pearl Millet and Cluster Bean Intercropping for Enhancing Fodder Productivity, Profitability and Land Use Efficiency (Bangladesh Journal of Botany, 2022)
An experiment was conducted to find out the suitable intercropping combination for pearl millet and cluster bean for higher fodder productivity, land use efficiency and profitability under Yamuna ravines of Uttar Pradesh, India. Nine treatments were evaluated which includes two treatment of sole crop (pearl millet and cluster bean) and seven intercropping combinations of pearl millet + cluster bean viz. 1 : 1, 2 : 1, 1 : 2, 2 : 2, 3 : 1, 1 : 3 and 3 : 3. Maximum value of total green fodder yield was obtained with intercropping of 3 : 1 row ratio; however, it was statistically at par with 2:1 row ratio. Further, maximum value of phosphorus and potassium uptake; LER, MAI, net return and benefit cost ratio was recorded with intercropping 2 : 1 row ratio. Thus, it was found that two row pearl millet + one row cluster bean (2 : 1) intercropping combination performed best in terms of yield, land use efficiency and profitability of fodder pearl millet and cluster bean.Bangladesh J. Bot. 51(1): 103-112, 2022 (March)